Does a lack of physical activity explain the rheumatoid arthritis lipid profile?. Issue 1 (December 2017) - AbouAssi, Hiba; Connelly, Margery; Bateman, Lori; Tune, K.; Huebner, Janet; Kraus, Virginia; Winegar, Deborah; Otvos, James; Kraus, William; Huffman, Kim
Abstract Background In rheumatoid arthritis (RA), cardiovascular risk is associated with paradoxical reductions in total cholesterol, low density lipoprotein-cholesterol (LDL-C), and high density lipoprotein-cholesterol (HDL-C). Concentrations of small LDL (LDL-P) and HDL (HDL-P) particles are also reduced with increased inflammation and disease activity in RA patients. Here we sought to identify which measure(s) of inflammation, disease activity and cardiometabolic risk contribute most to the RA-associated lipoprotein profile. Methods NMR lipoprotein measurements were obtained for individuals with RA (n  = 50) and age-, gender-, and body mass index (BMI)-matched controls (n  = 39). Groups were compared using 39 matched pairs with 11 additional subjects used in RA only analyses. Among RA patients, relationships were determined for lipoprotein parameters with measures of disease activity, disability, pain, inflammation, body composition, insulin sensitivity and exercise. Percentage of time spent in basal activity (<1 metabolic equivalent) and exercise (≥3 metabolic equivalents) were objectively-determined. Results Subjects with RA had fewer total and small LDL-P as well as larger LDL and HDL size (P  < 0.05). Among RA patients, pain and disability were associated with fewer small HDL-P (P  < 0.05), while interleukin (IL)-6, IL-18, and TNF-α were associated with LDL size (P  < 0.05). BMI, waist circumference, abdominal visceral adiposity and insulin resistance were associated with more total and small LDL-P, fewer large HDL-P, and a reduction in HDL size (P  < 0.05). Most similar to the RA lipoprotein profile, more basal activity (minimal physical activity) and less exercise time were associated with fewer small LDL-P and total and small HDL-P (P  < 0.05). Conclusions The RA-associated lipoprotein profile is associated with a lack of physical activity. As this was a cross-sectional investigation and not an intervention and was performed from 2008–13, this study was not registered in clinicaltrials.gov.